California State Hospital Violence Assessment and Treatment (Cal-VAT) guidelines. (14th August 2014) - Stahl, Stephen M.; Morrissette, Debbi A.; Cummings, Michael; Azizian, Allen; Bader, Shannon; Broderick, Charles; Dardashti, Laura; Delgado, Darci; Meyer, Jonathan; O'Day, Jennifer; Proctor, George; Rose, Benjamin; et al.
Abstract : Here we provide comprehensive guidelines for the assessment and treatment of violence and aggression of various etiologies, including psychotic aggression and impulsive aggression due to schizophrenia, mood disorders, ADHD, or trauma, and predatory aggression due to psychopathy and other personality disorders. These guidelines have been developed from a collection of prescribing recommendations, clinical trial results, and years of clinical experience in treating patients who are persistently violent or aggressive in the California Department of State Hospital System. Many of the recommendations provided in these guidelines employ off-label prescribing practices; thus, sound clinical judgment based on individual patient needs and according to institution formularies must be considered when applying these guidelines in clinical practice.